Serie "Unser Zeichen ist die Sonne", no. 8. Peters leitet als Jungaktivist den Bau eines Jugendloggers (1950)
Serie "Unser Zeichen ist die Sonne", no. 8. Peters leitet als Jungaktivist den Bau eines Jugendloggers.